Упростите выражение:

4
Ответов - 1
Вопрос задал ученик
Категории: Математика

Ответы


Гость
А) (x + 1 + 1/x-1) • 2x-2/x² = x•(x-1)+x-1+1/x-1 • 2(x-1)/x² = (x² - x + x) • 2/x² = x² • 2/x² = 2

b) (5x-4y / 5x+4y - 5x+4y / 5x-4y) : 16xy / 25x² - 16y² = (5x-4y)²-(5x+4y)² / (5x+4y)•(5x-4y) : 16xy / 25x² - 16y² = (-8y)•10x / (5x+4y)•(5x-4y) : 16xy / 25x²-16y² = -80xy / (5x+4y)•(5x-4y) : 16xy / 25x²-16y² = - 80xy/(5x + 4y)•(5x-4y) • 25x² - 16y²/16xy = - 5/(5x + 4y)•(5x-4y) • (5x-4y)•(5x+4y) = -5
Добавить ответ
Похожие вопросы
Топ Комментарии Архив
«    Апрель 2021    »
ПнВтСрЧтПтСбВс
 1234
567891011
12131415161718
19202122232425
2627282930 
Теги